The Impact of the Problem-Based Learning Model with Digital Student Worksheets on Student Learning Outcome at SMA PGRI Rumpin - Nina Mardiana; Saptina Retnawati (International Journal of Economics Education Research (IJEER), 2025)
Based on observations, the lack of teacher innovation in utilizing technological developments, such as the digital student worksheets used is still softcopy so that it is less attractive and does not meet the needs of students. This study intends to develop digital-based student worksheets in the Economics subject of SMA PGRI Rumpin. The methodology utilizes Quasi Experiment with Quantitative research methodology. A total of 42 grade X students from the 2023/2024 academic year participated in this study. The tool for data collection in this study was a question item instrument. Student learning outcome before the Problem Based Learning (PBL) model was applied were relatively low, the percentage of graduation in the experimental class was 16%. Likewise, the control class had a graduation percentage of 21%. After the PBL model was implemented, student learning outcome increased, the percentage of graduation in the experimental class was 100%. According to the independent sample t-test, the obtained significance value of 0.00 < 0.05 indicates that PBL model with digital student worksheets has an effect on student economics learning outcome at SMA PGRI Rumpin.